Investigation of the accuracy of BeiDou, QZSS and QZSS/BeiDou satellites configuration for short, medium and long baselines in the Asia-Pacific regions - Pirti, Atinc (SCIENDO, 2024)
The field of satellite navigation has seen significant advancements due to the fast development of multi-constellation Global Navigation Satellite Systems (GNSS). Around 150 satellites will be in service when all six systems - GPS, GLONASS, Galileo, BeiDou, QZSS, and NAVIC - are launched by 2030, offering both enormous potential and advantages for research and engineering applications. This study used an experiment on the accuracy, particularly for short, medium, long baselines (Wide Lane ambiguity solution) of the BeiDou, QZSS and QZSS/BeiDou combinations. It showed that with the integration of BeiDou/QZSS static measurements in the study region millimetre-centimetre accuracy for short, medium, and long baselines can be attained. Based on the results of this study, it can be concluded that the 1st (QZSS/BeiDou), 2nd (BeiDou), and 3rd (QZSS) strategies feature different horizontal accuracies for all categories. The obtained results with different satellite configurations for the Fixed-Wide-Lane integer ambiguity solution are compared with each other. Accuracy at the short baseline (BeiDou, QZSS, and BeiDou/QZSS satellites) was obtained in the range of 0.5-0.7 cm. For the medium baseline, it was computed around 1.8-82 cm. For the long baseline, the accuracy was 5.6-13.3 cm.
Keywords: BeiDou; accuracy; precision; improvement; QZSS; QZSS/BeiDou; GALILEO; GPS; BDS; SIGNAL; Remote Sensing